Concordance between stabilizing sexual selection, intraspecific variation, and interspecific divergence in Phymata. Issue 22 (12th October 2016) - Punzalan, David; Rowe, Locke
Abstract: Empirical studies show that lineages typically exhibit long periods of evolutionary stasis and that relative levels of within‐species trait covariance often correlate with the extent of between‐species trait divergence. These observations have been interpreted by some as evidence of genetic constraints persisting for long periods of time. However, an alternative explanation is that both intra‐ and interspecific variation are shaped by the features of the adaptive landscape (e.g., stabilizing selection). Employing a genus of insects that are diverse with respect to a suite of secondary sex traits, we related data describing nonlinear phenotypic (sexual) selection to intraspecific trait covariances and macroevolutionary divergence. We found support for two key predictions (1) that intraspecific trait covariation would be aligned with stabilizing selection and (2) that there would be restricted macroevolutionary divergence in the direction of stabilizing selection. The observed alignment of all three matrices offers a point of caution in interpreting standing variability as metrics of evolutionary constraint. Our results also illustrate the power of sexual selection for determining variation observed at both short and long timescales and account for the apparently slow evolution of some secondary sex characters in this lineage. Abstract : One apparent paradox is that although many studies detect strong contemporary selection and rapid microevolution, lineages typically exhibit long periods of stasis. A second, striking observation is that within‐species trait variability often correlates with the extent of between‐species trait divergence, leading some to invoke genetic constraints as an explanation. For a genus of insects, we show that data are consistent with an alternative explanation that (stabilizing sexual) selection shapes standing variation and that patterns of selection can themselves be conserved over macroevolutionary timescales.